Discovery Learning Assisted by Concept Maps: Improving Fifth-Grade Students' Learning Outcomes in Arts and Culture Education - Syachputri M, Winanda; Lagandesa, Yun Ratna; Lapasere, Sisriawan; Pendit, Sinta Satria Dewi; Isnayanti, Andi Nur; Wilade, Surahman (Papanda Publisher, 2025)
Traditional teacher-centered approaches in Arts and Culture education often result in passive learning and poor conceptual understanding among elementary students. This study investigated the effect of Discovery Learning assisted by concept maps on fifth-grade students' learning outcomes in Arts and Culture at SD Inpres 1 Kawatuna, Palu, Indonesia. A quasi-experimental one-group pretest-posttest design was employed with 27 fifth-grade students (19 males, 8 females) selected through saturated sampling. The intervention consisted of six 90-minute sessions integrating Discovery Learning with concept mapping activities. Data were collected using a validated cognitive achievement test (Cronbach's α = 0.717) and analyzed using paired-samples t-test and normalized gain analysis. The paired-samples t-test revealed statistically significant improvement from pretest (M = 56.48, SD = 13.52) to posttest (M = 85.70, SD = 7.89), with t(26) = 10.18, p < 0.001, and an exceptionally large effect size (Cohen's d = 2.54). Normalized gain analysis demonstrated medium-level effectiveness (g = 0.692, 69.2%). Discovery Learning assisted by concept maps significantly enhances Arts and Culture learning outcomes by fostering active engagement and systematic knowledge organization. The integrated approach addresses passive learning limitations and promotes deeper conceptual understanding, offering evidence-based pedagogical strategies for Indonesian elementary educators.